Occupational safety and health audit in small and medium industries ... [et al.] / [microfilm] - 406129 Sashi Kumar Supramaniam (Skudai : Universiti Teknologi Malaysia, 1998)
Project Paper (Bachelor of Engineering (Mechanical) - University Teknologi Malaysia, 1998